Inducing cells to disperse nickel nanowires via integrin-mediated responses. (12th March 2015) - Sharma, Anirudh; Orlowski, Gregory M; Zhu, Yuechen; Shore, Daniel; Kim, Seung Yeon; DiVito, Michael D; Hubel, Allison; Stadler, Bethanie J H
Abstract: We present non-cytotoxic, magnetic, Arg-Gly-Asp (RGD)-functionalized nickel nanowires (RGD–nanowires) that trigger specific cellular responses via integrin transmembrane receptors, resulting in dispersal of the nanowires. Time-lapse fluorescence and phase contrast microscopy showed that dispersal of 3 μ m long nanowire increased by a factor of 1.54 with functionalization by RGD, compared to polyethylene glycol (PEG), through integrin-specific binding, internalization and proliferation in osteosarcoma cells. Further, a 35.5% increase in cell density was observed in the presence of RGD–nanowires, compared to an increase of only 15.6% with PEG–nanowires. These results promise to advance applications of magnetic nanoparticles in drug delivery, hyperthermia, and cell separation where uniformity and high efficiency in cell targeting is desirable.